Immunohistochemistry on cell blocks a method for pre-operative diagnosis of papillary thyroid carcinoma by FNAC - Aljebori, Hussain A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Papillary thyroid carcinoma (PTC) is the commonest thyroid cancer. Cases in category- 5a of Bethesda system (suspicious for papillary carcinoma) are treated by surgical lobectomy followed by total thyroidectomy if histopathology confirms papillary carcinoma. In order to reduce surgical procedures to one this was conducted. Objectives: evaluation of role of immunohistochemistry in pre-operative diagnosis of papillary thyroid carcinoma on cell blocks. Materials and Method: Cell blocks were taken from cases labelled category-5a for histopathology and immunohistochemistry using three markers (CK-19, Thyro-peroxidase, and BRAFv600E mutation). Results: were highly sensitive, and specific. The use of more than markers increases sensitivity of the procedure. Conclusion: immunohistochemical stains on cell blocks is a reliable method for pre-operative diagnosis of papillary thyroid carcinoma.